Perceived social diversity and neighbourhood attachment: The role of intergroup ties and affective appraisals of the environment. Evidence from Poland. (December 2016) - Toruńczyk‐Ruiz, Sabina; Lewicka, Maria
Abstract: This paper investigates the relationship between perceived ethnic, age and income diversity and neighbourhood attachment, accounting for measures of objective diversity calculated for small, individualised neighbourhoods. With data from Warsaw in Poland, we examine whether neighbourhood ties with people of different ethnicity, age and income moderate the relationship between perceived diversity and attachment. We also test affective appraisals of the environment (excitement and irritation) as a mediator between perceived diversity and attachment. Perceived ethnic diversity was positively related to neighbourhood attachment, and this link was mediated by the emotion of excitement. Perceived income diversity undermined attachment regardless of the neighbourhood ties, and this link was not mediated by affective appraisals. Perceived age diversity was related to lower neighbourhood attachment only for individuals who had few ties with neighbours of different ages. We argue that the effects of diversity may depend on the socio‐cultural context, specifically on the level and meaning of diversity in a given society.